The Symbolic Meaning in the Reog Ponorogo Performance - Cahyani, Ika Nur; Nudin, Septian; Firdaus, Muhammad Jullyo Bagus (Journal of Southern Sociological Studies, 2025)
Reog Ponorogo is a traditional art form from East Java that has many symbols and cultural values. In addition to serving as entertainment, this performance conveys social, religious, and identity messages of the Ponorogo community. The purpose of this study is to discover the symbolic meaning of the main elements involved in the Reog performance, such as Singa Barong, Warok, Jathil, Gemblak, and the composition of music and dance. This research was conducted using a qualitative ethnographic approach through direct observation, interviews, and literature study. The results show that Singa Barong represents power and resistance against authority; Warok represents wisdom, spirituality, and guardian of morality; Jathil and Gemblak represent gender dynamics and changing cultural roles; and music and dance represent harmony and communal identity of the community. Overall, the Reog Ponorogo performance can be considered a representation of spirituality, resistance, and strong local identity in the modern world. By showing how local traditional symbols reflect social relationships and collective values of the community, this research contributes to cultural sociology studies.